Cultural Guidelines for Commercial Production of African Violets (Saintpaulia ionantha) - Jianjun Chen; Richard J. Henny (EDIS)
EP1096, a 5-page illustrated fact sheet by J. Chen and R. J. Henny, provides guidelines for the commercial production of African violets including propagation, cultural requirements, and common physiological problems. Published by the UF Department of Environmental Horticulture, February 2009.